2014
DOI: 10.1002/bsl.2135
|View full text |Cite
|
Sign up to set email alerts
|

Decision‐Making in Post‐acquittal Hospital Release: How Do Forensic Evaluators Make Their Decisions?

Abstract: A large number of individuals are acquitted of criminal charges after being found "not guilty by reason of insanity." Most of these individuals are hospitalized and later seek hospital discharge under a court-ordered provision called conditional release ("CR"). Courts rely on opinions from forensic evaluators to determine acquittees' readiness for CR. However, how evaluators make these decisions are unknown. Eighty-nine CR readiness evaluators from nine states were surveyed to understand which factors evaluato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(36 citation statements)
references
References 21 publications
0
35
1
Order By: Relevance
“…How evaluators decide to release NGRI patients conditionally or unconditionally is largely unknown. The study by Gowensmith, Bryant, and Vitacco (2014) investigated the procedures used by 89 forensic evaluators from nine states of the United States in conditional release readiness evaluations. The study showed that not only was there a lack of uniformity on any aspect of the decision making processes, evaluators de-emphasized important factors that have been empirically proven to be related to recidivism.…”
Section: Discussionmentioning
confidence: 99%
“…How evaluators decide to release NGRI patients conditionally or unconditionally is largely unknown. The study by Gowensmith, Bryant, and Vitacco (2014) investigated the procedures used by 89 forensic evaluators from nine states of the United States in conditional release readiness evaluations. The study showed that not only was there a lack of uniformity on any aspect of the decision making processes, evaluators de-emphasized important factors that have been empirically proven to be related to recidivism.…”
Section: Discussionmentioning
confidence: 99%
“…For example, it was shown that the historical HCR-20 scale , living arrangement (Marshall et al, 2014;Novosad et al, 2014), financial resources, personality disorder, substance use disorder and number of incidents in the CR programme, were related to revocation of CR (Manguno-Mire et al, 2014). As highlighted by several scholars (Crocker et al, 2014;Gowensmith et al, 2014;Green et al, 2014;Manguno-Mire et al, 2014), more research into empirically validated CR related risk and protective factors is needed to provide the clinical and legal practice with an empirical basis to standardize the decision-making process into CR and to develop successful CR programmes. The HOM meso-measurements can provide for this much needed evidence based working model to research empirically validated factors to augment our empirical understanding of CR patients as to enhance CR risk assessment and management programmes.…”
Section: Meso-levelmentioning
confidence: 96%
“…Yet, recidivism as a measure of effectiveness is often complicated due to methodological issues and incommensurable programmes, indications and groups. Methodological differences between studies in observation period, data source, recidivism definitions and criteria, complicate a wellconsidered comparison of recidivism rates which renders comparative studies across different offender groups and treatments invalid (Chambers et al, 2009;Falshaw, Bates, Patel, Corbett & Friendship, 2003;Hodgins, 2001;Liem, 2013;Lloyd, Mair & Hough, 1994;Maltz, 2001;Payne, 2007;Wartna, 2009). To acquire a comprehensive view on the outcome of penal interventions, a sound standardized methodological basis is a prerequisite (Payne, 2007;Wartna, 2009).…”
Section: Evaluation Research In Fmhmentioning
confidence: 98%
See 1 more Smart Citation
“…Empirical studies regarding insanity acquittees are relatively sparse. There has been a surge of studies in the literature in the past decade regarding conditional release of insanity acquittees – specifically, which factors are most predictive of success or failure for persons placed on conditional release (Green et al, ; Vitacco et al, ; Vitacco, Vauter, Erickson, & Ragatz, ) as well as which factors are typically considered by courts and evaluators in determining an insanity acquittees' readiness for conditional release (Gowensmith, Bryant, & Vitacco, ; Manguno‐Mire et al, ; McDermott et al, ). However, despite this increase in research attention, the volume of research on conditional release remains fairly slight.…”
mentioning
confidence: 99%